Overexpression of p53 Protein in Adenocarcinoma of the Pancreas. Issue 6 (9th January 2016) - DiGiuseppe, Joseph A.; Hruban, Ralph H.; Goodman, Steven N.; Polak, Miriam; van Den Berg, Frank M.; Allison, David C.; Cameron, John L.; Johan A. Offerhaus, G.
Abstract : Mutations in the p53 tumor suppressor gene are frequently identified in human neoplasms. These mutations may be associated with stabilization and, therefore, with overexpression of the p53 protein product as determined by immunohistochemical staining. Using a new antigen retrieval method and a polyclonal antibody to p53 (CM-1), the authors examined 48 formalin-fixed paraffin-embedded adenocarcinomas of the pancreas for overexpression of the p53 gene product. These 48 carcinomas were obtained from a series of patients with well-documented clinical histories and extensive follow-up. The carcinomas had been analyzed previously for K- ras gene mutations, tumor ploidy, and tumor proliferating index. Specific diffuse nuclear staining for the p53 protein was identified in 19 of the 48 (40%) infiltrating carcinomas examined. Focal or negative staining was seen in the remaining 29 cases (60%). In addition, 17 of the neoplasms contained synchronous in situ carcinomas; two (12%) of these displayed diffuse nuclear staining for the p53 protein. Overexpression of p53 was associated with aneuploidy ( P = .05), which had been a poor prognosticator in this series of adenocarcinomas of the pancreas. Although overexpression of p53 appeared to be associated with poor prognosis (hazard ratio, 1.8; P = .07), this was not statistically significant. Overexpression of p53 was not significantly associated with K- ras oncogene mutations or tumor proliferating index. The authors conclude that overexpression of the p53 protein occurs frequently in invasive adenocarcinomas of the pancreas and in some in situ carcinomas, as well.